Fingerprint analysis of placenta polypeptide injection by high performance liquid chromatography - Li Huang; Xiao-Man Wu; Yu Ji; Yu Wang (Elsevier, 2012)
Objective: To develop the representative fingerprint for the quality control of placenta polypeptide injection. Methods: The chromatographic separation was performed using a Phenomenex Gemini C18 column (250Â mmÃ4.6Â mm, 5Â Î¼m) maintained at 30Â Â°C. 0.1% aqueous trifluoroacetic acid (Solvent A) and acetonitrile contained 0.1% TFA (Solvent B) were used as mobile phase with a gradient elution. Detection wavelength was 280Â nm with the sample injection volume of 50Â Î¼L; the flow rate was 1.0Â mL/min. The fingerprints of different samples were investigated by similarity analysis. Results: Nine peaks were identified as the characteristic common peaks. The similarities of the fingerprints of the 10 batches of samples were above 0.992. Conclusion: This method showed high precision and good repeatability, and provided the basis for the improvement of the quality control of placenta polypeptide injection. Keywords: Placenta polypeptide injection, Fingerprint, Similarity analysis, High performance liquid chromatography